Tinjauan Maysir terhadap Permainan Capit Boneka - Lucy Lara MithaRusady; Hamda Sulfinadia; Aslan Deri Ichsandi (Saqifah: Jurnal Hukum Ekonomi Syariah, 2023)
The background to writing this scientific work is a game that has a new innovation now, namely the doll claw game. This game requires special skills and is quite difficult to win, so there are parties who feel disadvantaged and parties who benefit. The research questions in this case are: first, what is the practice of playing doll claws? secondly, what is the maysir concept of the puppet claw game? Third, what is the opinion of the ulama regarding the puppet claw game? To answer this question, the author conducted a library research from related books, journals, articles and websites. Then, in selecting supporting data, the author uses interview techniques and documentation in the form of pictures or photos related to the research object. The analysis that the author uses is a qualitative approach analysis technique. Based on the results of the research that has been carried out, the author can conclude, namely: first, the practice of playing doll claws begins with cards or coins that have been purchased by players on the game platform, then operated depending on the skill or skill of the player. Second, the puppet claw game seen from the concept of maysir or gambling fulfills an element of gambling. The elements in question are that there are parties who gain (win) and parties who suffer losses (lose), there are bets in the form of prizes and inserts in the game, players become addicted (continue) to play and the game is a matter of chance (testing their luck). Third, the opinion of scholars or experts regarding the law of playing doll claws is that it is haram, as well as many opinions that share the same view and research in previous journals. This creates several disadvantages which can actually bring losses.